Editorial: Suicide prevention in youth. Issue 4 (17th October 2022) - Berk, Michele S.
Abstract : Reducing deaths by suicide in youth is an urgent public health goal and effective treatment approaches remain limited. This editorial reviews new research published in this issue of Child and Adolescent Mental health that may inform youth suicide prevention efforts, including an open trial of a new, family‐focused group intervention for youth with suicidal ideation and findings showing that life problems associated with presentation to the emergency department for self‐harm vary by age and gender. The need for multi‐component treatments that have the flexibility to target a range of life problems/risk factors and to include families in treatment is discussed, along with the need to find a way to make such interventions scalable. Finally, this editorial addresses this issue's debate by discussing the role of mindfulness in dialectical behavior therapy for suicidal youth and the need to carefully monitor and further examine the effectiveness and safety of mindfulness with this patient population.